Psychometric Validation of the Persian Version of Short Form Self-Regulation Questionnaire in Community-Dwelling Older Adults - Motamed-Jahromi, Mohadeseh; Kaveh, Mohammad Hossein; Mohammadpour, Amin; Asadollahi, Abdolrahim (Frontiers in Psychology, 2022)
The aim of this study was to examine the validity and reliability of the Persian version of the Short Form Self-Regulation Questionnaire (SSRQ) and to determine its optimal cut-off point in Iranian community-dwelling older adults. This cross-sectional study was conducted among 500 older adults ≥60 years in two steps in Shiraz, Iran. The translation was performed using the forward-backward method. The psychometric properties were examined as the face and content validity based on the point of view of experts, construct validity based on exploratory and confirmatory factor analysis, convergent validity by assessing the relationship with the Generalized Self-Efficacy Scale (GSE-10), reliability using Cronbach’s alpha. A receiver operating characteristic curve (ROC) was plotted to confirm the cut-off point. Face and content validity were confirmed. The first stage of construct validity was performed using the kurtosis test and the exploratory factor analysis (EFA), and finally, only 20 items were loaded in four subscales with 76.34% of the total variance. The confirmatory factor analysis (CFA) indicated a good fit to the data (RMSEA = 0.059; CFI = 0.92; GFI = 0.89). Cronbach's alpha coefficient of SSRQ-20 improved to 0.87. A significant positive correlation was found between SSRQ-20 and GSE-10 (r = 0.44) that showed an acceptable convergent validity. The optimal cut-off score for differentiation between older adults in terms of self-regulation was 71. This study supports that the Persian version of SSRQ with 20 items is a valid and reliable tool for assessing self-regulation among Iranian community-dwelling older adults.